Role of Sb additive in the dielectric properties of f Se₉₀In₁₀ and Se₇₅In₂₅ glassy alloys - Sharma, J.; Kumar, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
In this paper, we report the effect of Sb additive on dielectric properties of two binary − InSe glassy systems, comparing the properties of a- Se₉₀In₁₀ a- Se₇₅In₂₅ and a Se₇₅In₂₅Sb₁₅ glassy alloys. The temperature and frequency dependence of ε′ and ε′′ in glassy Se₉₀In₁₀ , Se₇₅In₂₅, and Se₇₅In₂₅Sb₁₅ alloys are studied by measuring the capacitanceand dissipation factor within the frequency 1 kHz–5 MHz and temperature 300–350 K ranges. Debye like relaxation of dielectric behavior has been observed, which is in agreement with the Guintini theory of dielectric dispersion based on two electron hopping over a potential barrier and is applicable in the present case. ε′ , ε′′ and loss tangent (Tan δ) are found highly frequency and temperature dependent. Dependence of these dielectric parameters on the Sb metallic impurity has also been found in the present glassy system. The peculiar role of the third element Sb, as an impurity in the pure binary Se₉₀In₁₀ and Se₇₅In₂₅ glassy alloys, is also discussed in terms of electronegativity difference and covalent character between the elements used in making the aforesaid glassy system.